Applying activity theory in multiagency settings - Daniels, H (Moscow State University of Psychology and Education, 2016)
In this paper I explore the extent to which two approaches to the social formation of mind are compatible and may be used to enrich and extend each other. These are: Activity Theory (AT) as derived from the work of the early Russian psychologists, Vygotsky and Leontiev, and the work of the sociologist Basil Bernstein. The purpose is to show how Bernstein provides a language of description which allows Vygotsky’s account of social formation of mind to be extended and enhanced through an understanding of the sociological processes which form specific modalities of pedagogic practice and their specialized scientific concepts. The two approaches engage with a common theme namely the social shaping of consciousness, from different perspectives and yet as Bernstein acknowledges both develop many of their core assumptions from the work of Marx and the French school of early twentieth century sociology. The work of the Russian linguist is also be used to further nuance the argument applied in multiagency settings.